2018
DOI: 10.1158/0008-5472.can-17-3806
|View full text |Cite
|
Sign up to set email alerts
|

Combined MR Imaging of Oxygen Consumption and Supply Reveals Tumor Hypoxia and Aggressiveness in Prostate Cancer Patients

Abstract: The established role of hypoxia-induced signaling in prostate cancer growth, metastasis, and response to treatment suggests that a method to image hypoxia in tumors could aid treatment decisions. Here, we present consumption and supply-based hypoxia (CSH) imaging, an approach that integrates images related to oxygen consumption and supply into a single image. This integration algorithm was developed in patients with prostate cancer receiving hypoxia marker pimonidazole prior to prostatectomy. We exploited the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 42 publications
3
87
0
Order By: Relevance
“…Among different subtypes of MRI and MRS techniques, such as dynamic contrast-enhanced (DCE), blood oxygen level dependent (BOLD), diffusion-weighted (DW) MRI, 31 P-MRS, and 1 H-MRS, DCE–MRI clearly demonstrates the correlation of hypoxic state in tumors with radiotherapy outcome in patients with cervical cancer [62,63,64]. Recently, by exploiting the intravoxel incoherent motion signal in DW-MRI, both oxygen consumption and supply can be assessed, and the generated images on hypoxic tumors could help identify aggressive disease in prostate cancer [65]. Tumor hypoxia can also be inferred from the expression of various endogenous proteins, such as HIF-1α, glucose transporters-1 or -3, vascular endothelial growth factor-A, and carbonic anhydrase-9 [66,67,68,69,70,71].…”
Section: Hypoxiamentioning
confidence: 99%
“…Among different subtypes of MRI and MRS techniques, such as dynamic contrast-enhanced (DCE), blood oxygen level dependent (BOLD), diffusion-weighted (DW) MRI, 31 P-MRS, and 1 H-MRS, DCE–MRI clearly demonstrates the correlation of hypoxic state in tumors with radiotherapy outcome in patients with cervical cancer [62,63,64]. Recently, by exploiting the intravoxel incoherent motion signal in DW-MRI, both oxygen consumption and supply can be assessed, and the generated images on hypoxic tumors could help identify aggressive disease in prostate cancer [65]. Tumor hypoxia can also be inferred from the expression of various endogenous proteins, such as HIF-1α, glucose transporters-1 or -3, vascular endothelial growth factor-A, and carbonic anhydrase-9 [66,67,68,69,70,71].…”
Section: Hypoxiamentioning
confidence: 99%
“…An approximation of the original IVIM model is provided by the so-called simplified IVIM model [22] , [23] , [24] . As in tissue the condition is usually met, the first term of Eq.…”
Section: Dwi Models and Potential Biomarkersmentioning
confidence: 99%
“…A thorough evaluation of the signal decay curves is required to select optimal b -values for a particular model and anatomical site beforehand, for example by analyzing the goodness of fit when including different b -value combinations. An approach of performing such an evaluation is provided in [24] in the context of prostate cancer.…”
Section: Dwi Acquisition Detailsmentioning
confidence: 99%
“…Depending on the anatomical position, 4D-imaging to account for intra-fraction motion may be required to provide the technology for online adaptive image-guided radiation therapy [12][13][14][15]. Finally, a number of studies have identified multiparametric functional imaging as an ideal tool to assess dedicated molecular biomarkers containing information about biological characteristics or response prognosis with respect to outcome [16][17][18][19].…”
Section: Imagingmentioning
confidence: 99%